REVIEW ON FERTILITY PERFORMANCES OF LOCAL AND CROSSES OF EXOTIC BREED DAIRY CATTLE IN ETHIOPIA. - Kefale Getahun (Journal of Livestock Science and Production, 2023)
Review was carried out on fertility or reproductive performances of Ethiopian locals’ cattle and their Friesian and Jersey crosses. The objectives were to review research results on age of puberty, age at first calving, days open, postpartum anestrus interval, Service period, Number of Services per Conception and calving interval. The available review result showed that F1 Jersey and Friesian crosses had 7.65 and 5.89months shorter AFC than their F2 counterparts, respectively. Likewise, these crosses also had 12.63 and 11.35-months shorter AFC than that of local cows, respectively. Crossbred cows having 75% Friesian inheritance had comparable age at first calving with that of F1 Friesian and Jersey crosses. F1 Friesian crosseswere observed to have 37.67 and 33.96 days shorter calving interval as compared to crosses with 75% Frisian inheritances and F2 Friesian crosses, respectively. F1 Friesian and Jersey crosseshad 33.96 and 54.91 days shorter calving interval than their F2 counterparts, respectively. Crossbred cows having 75% Jersey had better reproductive performances than that of other crosses in reproductive traits considered except in age at first calving. Therefore, if the reproductive performance of local cows is to be improved, cows must be genetically upgraded to the level 50% exotic inheritances (Friesian/Jersey). Upgrading local cattle up to 75% exotic inheritance could also be done for better reproductive efficiency provided that the level of management is good enough to meet the relatively higher managerial demand of these animals. F1 crossbred dairy cattle is suitable to be used as dairy cattle under small holder management conditions and crossbred having 75% exotic blood level for urban and peri-urban dairy producers.